2020
DOI: 10.3390/ijerph17186524
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Social Integration and Utilization of Essential Public Health Services among Internal Migrants in China: A Multilevel Logistic Analysis

Abstract: This study investigated the association between social integration and utilization of essential public health services among internal migrants. Data were from the 2017 China Migrants Dynamic Survey. Social integration was measured through four dimensions: economic integration, structural integration, sociocultural adaptation, and self-identity. Multilevel logistic regressions were used taking into account heterogeneity in the level of regional development. The utilization of health records and health education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…As far as migrating characteristics, some studies show that the longer migrants stay at the destination, the higher the degree of social integration and the establishment rate of health records [7,18], which is different from the results in model 1. We introduce the interaction terms between length of migration and household registration status, together with length of migration and educational attachment to further explore whether the impact of length of migration on the establishment rate of health records is influenced by the household registration status and educational attachment.…”
Section: Marital Statusmentioning
confidence: 65%
See 2 more Smart Citations
“…As far as migrating characteristics, some studies show that the longer migrants stay at the destination, the higher the degree of social integration and the establishment rate of health records [7,18], which is different from the results in model 1. We introduce the interaction terms between length of migration and household registration status, together with length of migration and educational attachment to further explore whether the impact of length of migration on the establishment rate of health records is influenced by the household registration status and educational attachment.…”
Section: Marital Statusmentioning
confidence: 65%
“…The impact of the special household registration system on the utilization of BPHS in China has also been researched. Compared with migrants with rural household registration, migrants with urban household registration had a higher likelihood to utilize BPHS [5,7,16,17]. Other factors were also explored in the studies of this research domain, such as social integration, age, ethnicity, employment status, current health situation, medical insurance coverage, rage of migrating, family income were also associated with the utilization of BPHS [7,13,16,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors with minor importance also were documented in the early research. Early studies reported that market-oriented financing reforms of public health services ( 35 ), clear and detailed protocols ( 36 ), structural social capital ( 37 ), household registration ( 38 ), satisfaction with the attitude of primary health care workers ( 39 ), and social integration ( 40 ) were responsible for an increased utilization of local public health services among domestic migrants in China.…”
Section: Discussionmentioning
confidence: 99%
“…The data we used were taken from the China Migrants Dynamic Survey (CMDS) in 2017, conducted in all the provinces by the National Health and Family Planning Commission of People's Republic of China. CMDS focused on internal migrants, who were above 15 years old and have been living in destination cities for at least 1 month but without their household registration (Hukou) (excluding students, soldiers, and households where one of the spouses has the local hukou) ( 27 ). A three multiple-stage and Probability-Proportional-to-Size sample methods were used to size the samples.…”
Section: Methodsmentioning
confidence: 99%